Examining the Teaching Competencies and their relation to the Mathematics Performance of Primary School Students - Libiado, Flordeliza D; Canuto, Peter Paul L (Future Science / FSH-PH Publications, 2023)
The teachers' role is to influence, engage, commit, and support the students toward a positive outlook of Mathematics as a discipline. This suggests that students' understanding, acknowledgment, and achievement in the discipline primarily depend on the teachers. Considering teachers' role and students' achievement, the study aims to determine the teaching competencies affecting teachers' performances and their association with the students' mathematics performance. The study utilized a survey questionnaire, and the obtained data were analyzed using descriptive and inferential analysis. The respondents involved 51 primary school teachers from Grades 4-6 in Tinoc District, Tinoc, Ifugao, Philippines. Results shows that the teachers always observed the teaching competencies in their Mathematics teaching. Conclusively, assessment of learning is the most observed competency, followed by personality traits, teaching pedagogy, and instructional material (IMs) utilization. Results also shows no significant difference in the teaching competencies based on demographic factors. Moreover, results indicates a lower average (45.80%) Mathematics performance of the primary school students. Consequently, further analysis reveals a non-association between the teaching competencies and the students' mathematics performance. These results infer that the students' mathematical ability is at the beginning level, and mathematical concepts are not fully grasped. It also indicates that teachers are not able to affect the students' performances regardless of always observing the competencies. Nonetheless, a firm view of the teacher’s ability to impact the students' understanding and achievement in mathematics is still sustained.